Enhancing Village Government Capacity to Manage Village Funds for Achieving Sustainable Development Goals in Rural Communities - Magfiroh, Diana (Politeknik Siber Cerdika Internasional, 2025)
The implementation of Village Fund in Indonesia faces significant challenges related to institutional capacity variations among village governments, which affects the achievement of sustainable development goals at the village level. This study analyzes the influence of village government institutional capacity on Village Fund implementation effectiveness for achieving SDGs, identifying key capacity dimensions and institutional capacity typologies. This study employs mixed methods research with an explanatory sequential design, integrating quantitative and qualitative approaches. Institutional capacity, comprising six dimensions (structural and organizational capacity, human resource competency, financial management systems, participatory planning, information technology, and governance and accountability), contributes 64.7% to implementation effectiveness, with mentoring quality as the strongest moderating factor (4.8%). Cluster analysis identifies four typologies: Innovator (21.7%), Conventional (36.7%), Developing (26.4%), and Weak (15.3%), each requiring differentiated interventions. This research provides an evidence-based diagnostic framework for policymakers to design targeted institutional strengthening programs, optimizing Village Fund utilization and accelerating sustainable village development.